Acquired factor VII deficiency associated with acute myeloid leukemia. Issue 3 (April 2015) - Anoun, Soumaya; Lamchahab, Mouna; Oukkache, Bouchra; Qachouh, Maryam; Benchekroun, Said; Quessar, Asmaa
Abstract : Isolated acquired factor VII deficiency is a rare coagulopathy. It has been reported in 31 patients with malignancy, sepsis, postoperatively, aplastic anemia, and during bone marrow transplantation. We discuss, through a new case of acquired factor VII deficiency, the characteristics of this disease when it is associated with acute myeloid leukemia. Acquired factor VII deficiency in hematological diseases can be caused by intensive chemotherapy, infections, or hepatic dysfunction. The best treatment in developing countries remains corticosteroids associated with plasma exchange, frozen plasma, and antibiotics.